2009
DOI: 10.1016/j.jvs.2009.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural hemoglobin predicts outcome in peripheral vascular disease patients undergoing percutaneous transluminal angioplasty

Abstract: Anemia is a common comorbid condition in patients with advanced PVD. Preprocedural hemoglobin could be used in clinical practice to risk stratify patients with advanced PVD who are being considered for PTA. Correction of anemia before PTA in patients with Rutherford category 4 and 5 PVD may improve long-term outcome. Further investigation is needed regarding the optimization of preprocedural hemoglobin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
(19 reference statements)
2
11
0
Order By: Relevance
“…6,11,2831 Gupta et al demonstrated that preoperative anemia (HCT < 39%) was associated with a higher rate of 30-day mortality (2.4% vs. 1.2%) and cardiac events (2.3% vs. 1.2%) compared to non-anemic elderly patients undergoing elective vascular procedures in NSQIP. 29 A retrospective analysis of patients between 1990–2006 from a single institution also reported that the degree of anemia was inversely associated with not only 30-day but also 5-year MACE in 1,211 vascular patients.…”
Section: Discussionmentioning
confidence: 99%
“…6,11,2831 Gupta et al demonstrated that preoperative anemia (HCT < 39%) was associated with a higher rate of 30-day mortality (2.4% vs. 1.2%) and cardiac events (2.3% vs. 1.2%) compared to non-anemic elderly patients undergoing elective vascular procedures in NSQIP. 29 A retrospective analysis of patients between 1990–2006 from a single institution also reported that the degree of anemia was inversely associated with not only 30-day but also 5-year MACE in 1,211 vascular patients.…”
Section: Discussionmentioning
confidence: 99%
“…In one recent retrospective study of 101 patients undergoing nonemergent lower extremity PVI, preprocedural H level was shown to be associated with an unfavorable 14-month peripheral vascular outcome (a composite of all-cause mortality, limb amputation, and target lesion revascularization) [4]. A preprocedural H level of 10.5 AE 0.7 g/dl when compared with a H level of 13.9 AE 0.9 g/dl was associated with a 4.17 increased odds of an adverse peripheral vascular outcome (OR: 4.17; 95% CI: 1.56-11.16; P ¼ 0.004) and a preprocedural H level of 12.0 AE 0.4 g/dl when compared to a H level of 13.9 AE 0.9 g/dl was associated with a 2.99 times increased odds of an adverse peripheral vascular outcome (OR: 2.99; 95% CI: 1.14-7.53; P ¼ 0.03).…”
Section: Discussionmentioning
confidence: 99%
“…1 g/dl in patients undergoing percutaneous coronary intervention is associated with adverse outcomes [2,3]. The prognostic significance of baseline H in patients undergoing peripheral vascular interventions (PVI) is uncertain [4]. We evaluated the midterm prognostic significance of serum H by a retrospective analysis of a consecutive series of patients undergoing percutaneous PVI.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia was also found to be a strong predictor of both repeat EI including TVR and death in female patients with PAD. As a population, patients with PAD have been shown to have a high prevalence of anemia 24 . Poorer outcomes in anemic patients after PCI have been attributed to higher frequencies of cardiac comorbidities, poor nutritional status, and increasing patient age 25–27 .…”
Section: Discussionmentioning
confidence: 99%